Peculiarities of modulating effects of “Myroslava” and “Khrystyna” mineral waters on neuroendocrine-immune complex and metabolism in patients of Truskavets’ spa - Popovych, Igor; Gozhenko, Anatoliy; Hrytsak, Myroslava; Popovych, Dariya; Badiuk, Nataliya; Zukow, Walery (Journal of Education, Health and Sport, 2022)
Background. Earlier we found effects on the neuroendocrine-immune complex and metabolism, which are common to the mineral waters "Myroslava" and "Khrystyna", instead different from the effects of Naftussya water. The purpose of this article is to find the specific effects of these waters. Materials and Methods. The object of clinical-physiological observation were 22 men aged 23-70 years, who underwent rehabilitation treatment of chronic cholecystitis and pyelonephritis in remission in the Truskavets’ spa. The examination was performed twice, before and after a 7-10-day course of balneotherapy. Half of the patients received bioactive water Naftussya and sulfate-chloride sodium-magnesium mineral water "Myroslava" (M 5 g/L), and the other half - Naftussya and "Khrystyna" (M 10 g/L). The subject of the study were the parameters of the neuroendocrine-immune complex, microbiota, cholekinetics and metabolism. Results. Screening revealed specific changes in 37 parameters grouped into 5 patterns. The first pattern combines 11 parameters that decrease under the influence of "Myroslava" water (Myr), while increase under the influence of "Khrystyna" water (Khr). For the other 7 parameters of the second pattern, Myr acts similarly, while Khr is ineffective. Both mineral waters have a stimulating effect on 8 parameters, while Myr is inferior to Khr. Myr has a upregulating effect on 9 parameters of the fourth pattern, while Khr has a downregulating effect. Finally, sodium excretion and leukocyturia are reduced under the influence of both waters, but to a greater extent under the influence of Khr. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa have both common and specific favorable modulating neuroendocrine, metabolic and immune effects on patients with chronic cholecystitis and pyelonephritis.